The Value of Umbilical Cord Blood Bilirubin Measurement in Predicting the Development of Significant Hyperbilirubinemia in Healthy Newborn (Bangladesh Journal of Child Health, 2010)
The present study was conducted to investigate the predictability of early serumbilirubin levels on the subsequent development of neonatal hyperbilirubinemia. Forthis purpose 84 healthy newborn infants were enrolled and followed up for first 5 daysof life. Study subjects were divided into two groups. Group-I consisted of 71 subjects,who did not develop significant hyperbilirubinemia (bilirubin 17mg/dl) during the follow up. Of the enrolled subjects, 46 (55%) were male and rest 38(45%) were female; 64 (76%) were term babies and 20 (24%) were pre-term babies.Significantly higher percentage of pre-term babies developed hyperbilirubinemia. ROC(receiver operating characteristic) analysis demonstrates that the critical value ofcord blood bilirubin >2.5mg/dl had the high sensitivity (77%) and specificity (98.6%)to predict the newborn who would develop significant hyperbilirubinemia. At this levelthe negative predictive value was 96% and positive predictive value 91%. In oursetting infants having umbilical cord blood total serum bilirubin (TSB) >2.5 mg/dlshould be followed up strictly either in hospital or as an outpatient department on day5 if practicable. Infants having TSB